Cervicovaginal Immune Activation in Zambian Women With Female Genital Schistosomiasis - Sturt, Amy S.; Webb, Emily L.; Patterson, Catriona; Phiri, Comfort R.; Mweene, Tobias; Kjetland, Eyrun F.; Mudenda, Maina; Mapani, Joyce; Mutengo, Mable M.; Chipeta, James; van Dam, Govert J.; Corstjens, Paul L. A. M.; et al. (Frontiers in Immunology, 2021)
HIV-1 infection disproportionately affects women in sub-Saharan Africa, where areas of high HIV-1 prevalence and Schistosoma haematobium endemicity largely overlap. Female genital schistosomiasis (FGS), an inflammatory disease caused by S.haematobium egg deposition in the genital tract, has been associated with prevalent HIV-1 infection. Elevated levels of the chemokines MIP-1𝛂 (CCL-3), MIP-1𝛃 (CCL-4), IP-10 (CXCL-10), and IL-8 (CXCL-8) in cervicovaginal lavage (CVL) have been associated with HIV-1 acquisition. We hypothesize that levels of cervicovaginal cytokines may be raised in FGS and could provide a causal mechanism for the association between FGS and HIV-1. In the cross-sectional BILHIV study, specimens were collected from 603 female participants who were aged 18-31 years, sexually active, not pregnant and participated in the HPTN 071 (PopART) HIV-1 prevention trial in Zambia. Participants self-collected urine, and vaginal and cervical swabs, while CVLs were clinically obtained. Microscopy and Schistosoma circulating anodic antigen (CAA) were performed on urine. Genital samples were examined for parasite-specific DNA by PCR. Women with FGS (n=28), defined as a positive Schistosoma PCR from any genital sample were frequency age-matched with 159 FGS negative (defined as negative Schistosoma PCR, urine CAA, urine microscopy, and colposcopy imaging) women. Participants with probable FGS (n=25) (defined as the presence of either urine CAA or microscopy in combination with one of four clinical findings suggestive of FGS on colposcope-obtained photographs) were also included, for a total sample size of 212. The concentrations of 17 soluble cytokines/chemokines were quantified by a multiplex bead-based immunoassay. There was no difference in the concentrations of cytokines/chemokines between participants with and without FGS. An exploratory analysis of those women with a higher FGS burden, defined by ≥2 genital specimens with detectable Schistosoma DNA (n=15) showed, after adjusting for potential confounders, a higher Th2 (IL-4, IL-5, and IL-13) and pro-inflammatory (IL-15) expression pattern in comparison to FGS negative women, with differences unlikely to be due to chance (p=0.037 for IL-4 and p<0.001 for IL-5 after adjusting for multiple testing). FGS may alter the female genital tract immune environment, but larger studies in areas of varying endemicity are needed to evaluate the association with HIV-1 vulnerability.